Influence of Edible Coating on the Drying and Quality of Papaya (Carica papaya) - Garcia, Carolina Castilho; Caetano, Lidimara Cassia [UNESP]; Silva, Keila de Souza [UNESP]; Mauro, Maria Aparecida [UNESP] (Springer, 2014)
The edible coating applied to food pieces prior to hot air drying is a technology that can improve the nutritional and sensory qualities of dehydrated products. The effects of the pectin coating technique on the drying efficiency and quality of papaya slices of the Formosa cultivar were investigated, determining the cell structure, color, and vitamin C contents of the fresh and dried fruits, with and without a pectin coating. The drying kinetics was evaluated based on Fick's Law. The analytical solution for a plane sheet was used to estimate the water effective diffusion coefficients, and, in order to take into account shrinkage during drying, the average and variable thicknesses were considered in an approximate manner. Diffusion modeling presented a better fit when considering the thickness of the slices as variable. Regarding fruit quality, the coating applied to papaya slices before drying enhances vitamin C retention in comparison to papaya dried without coating, showing that pectin coating efficiently prevented oxidation of this bioactive compound. In addition, the moisture diffusivity of the coated samples was higher than that of the non-coated slices, due to the hydrophilic nature of the pectin. Light and transmission electron microscopy images revealed intense rupturing of the cell membranes in the dried tissues. The cell tissue arrangement in the coated papaya slices was similar to that found in the fresh papaya slices, before and after drying.
Keywords: Papaya; Hot air drying; Effective diffusion coefficients; Edible coating; Vitamin C; Microscopic features